LABEL AND CONTAINER - FURUSAWA, Hiroki (2025)
A label is provided that includes layers; a base film, a thermal layer, and a heat-shrinkable layer. This label is adhered to the top seal of a container. When this label-adhered container is heated in a microwave oven, the thermal layer generates heat through microwave absorption, and heat thus generated serves to heat and soften the base film, heat-shrinkable film and top seal. The heat-shrinkable film shrinks under heat, opening notches penetrating through the label. The top seal thus affected by heating is further subject to a stress applied in response to the notches being opened, and a heated and softened portion of the top seal is also affected by an increasingly higher internal pressure. As a result, holes are formed in the top seal.